Minat Siswa Terhadap Pembelajaran Penjas Berbasis E-Learning Pada Masa Pandemi Covid-19 Di SMKN 1 Batujaya - Ghalib Rizky Fajar; Rekha Ratri Julianti; Siswanto Siswanto (Peneliti.net, 2021)
The purpose of this study was to find out how much interest in class X students at SMKN 1 Batujaya towards e-learning-based physical education learning. This research is a type of quantitative research (non-experimental) with a descriptive approach. According to (Arikunto, 2006: 243), stated that descriptive research is non-hypothetical research, so the research step does not formulate hypotheses. In this study using a survey method with data collection techniques with a questionnaire. From the results of this study, it is known that the level of student interest in physical education learning at SMKN 1 Batujaya is in the category of 7 students (3.72%) in the very good category, 53 students (28.19%) in the good category, 60 students (31.91%) ) in the sufficient category, 51 students (27.13%) in the poor category, 17 students (9.04%) in the very poor category. The highest frequency is in the sufficient category, so it can be concluded that the level of student interest in E-learning-based physical education is categorized as